Strategic Intelligence and its Role in Improving the Quality of Banking Service: دراسة تحليلية لآراء عينة من العاملين في بعض المصارف بمحافظه بابل - اميمة حميد العادلي; جنان محمد خضير (Iraqi Journal for Administrative Sciences, 2024)
The aim of this research is to identify the role that strategic intelligence plays in its dimensions (foresight / organizational thinking / strategic vision / partnership / motivation) in improving the quality of banking service by its dimensions (reliability / response / trust, emphasis / motivation / partnership). The nature of the relationship between strategic intelligence and improving the quality of banking service Two hypotheses were developed 1-There is a significant correlation between strategic intelligence in all its dimensions (outlook / structured thinking / vision / partnership / motivation) and improving the quality of banking service in all its dimensions (reliability / response / emphasis / empathy / concrete). 2 - the existence of a significant impact between strategic intelligence in all dimensions (outlook / structured thinking / vision / partnership / motivation) and improve the quality of banking service in all dimensions (reliability / response / emphasis / sympathy / concrete). The questionnaire consisted of (51) items as the main tool for collecting data on the sample of the research represented by workers in a number of private banks registered in the Iraqi market for securities where the number of sample members (50) and used a set of statistical means as simple correlation coefficient and multiple to measure the correlation between (T) to determine the significance of the simple correlation relationship, the simple regression analysis and the f () test to determine the significance of the regression equation. R² was also used to explain the effect of the independent variable in the dependent variable. :The management of the surveyed banks has the ability and ability to develop its strategy in the long run by investing strategic intelligence in support of its business. :The investigated banks provide new ways to learn and acquire knowledge for the purpose of strategic integration as they work hard to design and invent intelligent solutions and stereotypes.The main recommendations of the study are: -The need to study the banks investigating the obstacles that prevent the use of strategic intelligence of this importance in achieving the quality of banking service. -the need to use strategic intelligence for officials to achieve flexibility in quality of service and interaction with the external environment to achieve the most important results.